Design and synthesis of tricyclic terpenoid derivatives as novel PTP1B inhibitors with improved pharmacological property and in vivo antihyperglycaemic efficacy - Lingling Yang; Feng Chen; Cheng Gao; Jiabao Chen; Junyan Li; Siyan Liu; Yuanyuan Zhang; Zhouyu Wang; Shan Qian (Taylor & Francis Group, 2020)
Overexpression of protein tyrosine phosphatase 1B (PTP1B) induces insulin resistance in various basic and clinical research. In our previous work, a synthetic oleanolic acid (OA) derivative C10a with PTP1B inhibitory activity has been reported. However, C10a has some pharmacological defects and cytotoxicity. Herein, a structure-based drug design approach was used based on the structure of C10a to elaborate the smaller tricyclic core. A series of tricyclic derivatives were synthesised and the compounds 15, 28 and 34 exhibited the most PTP1B enzymatic inhibitory potency. In the insulin-resistant human hepatoma HepG2 cells, compound 25 with the moderate PTP1B inhibition and preferable pharmaceutical properties can significantly increase insulin-stimulated glucose uptake and showed the insulin resistance ameliorating effect. Moreover, 25 showed the improved in vivo antihyperglycaemic potential in the nicotinamide-streptozotocin-induced T2D. Our study demonstrated that these tricyclic derivatives with improved molecular architectures and antihyperglycaemic activity could be developed in the treatment of T2D.